Synthesis, characterization and effects of thermal treatment of ZnO-AND CdO-based nanomaterials - Al-Hada, Naif Mohammed Ali (2015)
Nanoscience can simply be defined as the study and understanding of nanomaterials and their manipulation at atomic, molecular and macromolecular scales where properties vary significantly from those at a macroscopic scale. Nanotechnology on the other hand can be defined as the design, production and application of nanostructured devices and systems by controlling shape and size at a nanometer scale. Nanomaterials could be defined as the materials with at least one of its dimensions in the range of a nanometer. The study of nanomaterials is very interesting and important because at nanoscale, materials have fundamentally unique properties compared to their bulk due to increased surface area to volume ratios. The metallic compounds which formed with metal and oxygen in the form of oxide ion (O2-) are called metal oxide." They a named in two words where first word is the name of metal with oxidation number in parenthesis followed by oxide. Nanomaterials including metal oxide nanoparticles are of scientific and technological importance due to their unique physical and chemical properties arise from their nanoscale dimension and large number of surface atoms. As their properties are dependent on large surface area to volume ratio and quantum confinement effect, they have potential applications in almost every field of human endeavor. PVP displays capping ability (capping agent) which plays significant role in the synthesis of metal oxide nanoparticles. It is however realized that PVP controls the growth of the nanoparticles with the variation of its concentration, prevents the agglomeration, improves the crystallinity and brings about homogeneity and uniformity in the shape of nanoparticles. From the prepared ZnO results, the XRD diffraction patterns at calcination temperatures 500-650 oC showed that the crystallite size was in the range of 18–41 nm with hexagonal structure. These results were in agreement with the transition electron microscopy results which showed that the formation of ZnO in nanoscale size. The average particle size determined by TEM images were found to increase from 19 to 43 nm with increase in calcination temperatures. The FTIR results confirmed the removal of polymer and the presence of metal oxide nanoparticles at calcination temperatures 500-650 oC. The elemental composition of the samples obtained by EDX spectroscopy has further evidenced the formation of ZnO nanoparticles. In addition, the optical band gap of the samples was calculated using Kubelka-Munk model for calcination temperatures 500-650 oC. The band gap varied from 3.27 to 3.23 eV for calcination temperatures 500-650 oC. A decrease in the energy band gap with increasing calcination temperatures is attributed to the increase in the particle size. It is believed that as the particle size increases, the number of atoms that form a particle also increase, which consequently render the valence and conduction electrons more attractive to the ions core of the particles, and hence decreasing the band gap of the particles. The PL spectra at calcination temperatures 500-650 oC showed that the increment in the intensity with increasing calcination temperatures is attributed to the increase in the particle size. From the prepared CdO results, the XRD diffraction patterns at calcination temperatures 500-650 oC showed that the crystallite size was in the range of 13–47 nm with cubic center face structure. These results were in agreement with the transition electron microscopy results which showed the formation of CdO in nanoscale size. The average particle size determined by TEM was found to increase from 18 to 48 nm with increase in calcination temperature. The FTIR results confirmed the removal of polymer and the presence of metal oxide nanoparticles at calcination temperatures 500-650 oC. The elemental composition of the samples obtained by EDX spectroscopy has further evidenced the formation of CdO nanoparticles. In addition, the optical band gap of the samples was calculated using Kubelka-Munk model for calcination temperatures 500-650 oC. The band gap was found to vary from 2.14 to 2.01 eV. A decrease in the energy band gap with increasing calcination temperatures is attributed to the increase in the particle size. The PL spectra at calcination temperatures 500-650 oC showed that the increment in the intensity with increasing calcination temperatures is attributed to the increase in the particle size. From the prepared (ZnO)x(CdO)1-x nanosheets results, the XRD diffraction patterns at calcination temperatures 500-650 oC showed that the crystallite size was in the range of 15-25 nm for (ZnO)0.2(CdO)0.8 and 13-32 nm for ZnO)0.8(CdO)0.2 with hexagonal and cubic structures respectively. The average particle size determined by TEM were found to increase with calcination temperatures from 14-26 nm for (ZnO)0.2(CdO)0.8 and 16-40 nm for ZnO)0.8(CdO)0.2. The FTIR results confirmed the removal of polymer and the presence of metal oxide nanoparticles at calcination temperatures 500-650 oC. The elemental composition of the samples obtained by EDX spectroscopy has further evidenced the formation of (ZnO)x(CdO)1-x nanosheets In addition, the optical band gap of the samples was calculated using Kubelka-Munk model for calcination temperatures 500-650 oC. The band gap varied from 2.83-3.22 to 2.68-3.09 eV for calcination temperatures 500-650 oC. A decrease in the energy band gap with increasing calcination temperatures is attributed to the increase in the particle size. It is believed that as the particle size increases, the number of atoms that form a particle also increase, which consequently render the valence and conduction electrons more attractive to the ions core of the particles, and hence decreasing the band gap of the particles. The PL spectra at calcination temperatures 500-650 oC showed that the increment in the intensity with increasing calcination temperatures is attributed to the increase in the particle size. A thermogravimetric analyser (TGA) was used to study thermal stability and the temperature at which polymer could be remove from the samples during calcination. The maximum decomposition of the polymer was found at 485 oC.